Regional Population Expenditure for Foodstuffs in the Russian Federation: Componential and Cluster Analyses - Guzairov, Murat Bakeevich; Degtyareva, Irina Viktorovna; Makarova, Elena Anatolyevna (Economy of Regions, 2015)
We article describes the solving of the problem of conducting the componential and cluster analyses of population expenditure for foodstuffs as one of the most important components of the standard of living. The purpose of the analysis is to develop the regional clusters of the Russian Federation, which vary in the structure of household expenditure for foodstuffs. The foodstuffs are presented in absolute units taking into integral account the standard of living index. We methods of intellectual analysis such as component and cluster analyses are applied as the research methods. We procedure for the data intellectual analysis based on the interconnected performance of component and cluster analyses is proposed. We procedure of the data intellectual analysis considers the interrelation between the results received by different methods, and also the possibility to return to the previous method for the purpose of repeating the analysis to specify consistently the clusters composition. Few clusters of the wealthy regions characterized by the high and average level of expenditure for foodstuffs are revealed as well as the quite many clusters of not enough wealthy and not wealthy regions characterized by the low level of expenditure for foodstuffs. It is shown that the growth of standard of living characterized by the size of a gross regional product per capita is followed by the growth of the Gini coefficient, which indicates both the inequality of income distribution and reduction in expenditure for low-value foodstuffs. We results of the analysis can be applied for the development of the decision making support system intended for the analysis of the scenarios of macroeconomic regulation in the field of income policy for the purpose of increasing the standard of living of the population. We analysis of the population expenditure for foodstuffs has allowed to reveal the cluster structure of the regions of the Russian Federation, to show it according to the generalized indications, to formulate the specific characteristics of the clusters of the regions and important management decisions.